THE ROLE OF THE MINISTRY OF RELIGION IN PROMOTING RELIGIOUS MODERATION IN THE DIGITAL ERA - A, Sulastri; Fitri, Humaira Nurwani; Zafira, Nurul; Syari, Sabila Rahma; Prawardani, Diah Arum (Proceeding International Seminar of Islamic Studies, 2024)
Religious moderation is an important key in minimizing radical acts and extremism in religion in Indonesia. The Ministry of Religion is an important element in being responsible for religious harmony in Indonesia. The program to strengthen religious moderation was also intensified in 2019 by the Ministry of Religion. The author uses a qualitative research approach for this research method. Based on the results of research conducted by researchers, it is "The Role of the Ministry of Religion in Religious Moderation in the City of Medan". The Mayor of Medan advised that we must maintain harmony and establish harmony between religious communities so that Medan City can become a harmonious city for all believers. "How to Promote Religious Moderation" Use social media to spread the message of religious moderation, educate the public, and create a positive platform for communication "The Ministry of Religion's goal is to promote religious moderation in the Digital Era" to be able to develop an online educational platform to deliver religious moderation material, utilizing technology digital as an easily accessible learning tool. Through campaigns on social media, the ministry can spread messages of religious moderation, promote interfaith dialogue, and share inspiring stories that show harmony in life amidst differences in beliefs.